Different functions of hyperpolarization-activated cation channels for hippocampal sharp waves and ripples in vitro - Kranig, Simon A.; Duhme, Nana; Waldeck, Clemens zu; Draguhn, Andreas; Reichinnek, Susanne; Both, Martin (Neuroscience, 2013)
Hyperpolarization-activated currents (Ih) affect multiple neuronal functions including membrane potential, intrinsic firing properties, synaptic integration and frequency-dependent resonance behavior. Consistently, Ih plays a key role for oscillations at the cellular and network level, including theta and gamma oscillations in rodent hippocampal circuits. Little is known, however, about the contribution of Ih to a prominent memory-related pattern of network activity called sharp-wave-ripple complexes (SPW-R). Here we report that pharmacological suppression of Ih induces specific changes in SPW-R in mouse hippocampal slices depending on the specific drug used and the region analyzed. Spontaneous generation of the events was reduced by blocking Ih whereas the amplitude was unaffected or increased. Interestingly, the superimposed ripple oscillations at ∼200Hz persisted with unchanged frequency, indicating that Ih is not critical for generating this rhythmic pattern. Likewise, coupling between field oscillations and units was unchanged, showing unaltered recruitment of neurons into oscillating assemblies. Control experiments exclude a contribution of T-type calcium channels to the observed effects. Together, we report a specific contribution of hyperpolarization-activated cation currents to the generation of sharp waves in the hippocampus.
Available online 1 November 2012
Gesehen am 30.03.2021